The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.livsci.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of grazing behaviour, dietary overlap and performance in non-lactating domestic ruminants grazing on marginal heathland areas

Abstract: During the years 2000-2001, 7 non-lactating beef cows, 40 ewes and 40 does were managed in mixed grazing on a natural heathland vegetation plot (22 ha) with 20% improved pasture (perennial ryegrass) on a hill (1000 m a.s.l.) experimental farm located in the NW of Spain. Samples of faeces and vegetation components were collected monthly to estimate diet selection, using the alkane markers, and diet overlapping level. Animals were weighed monthly to quantify live weight changes and performance of the three lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 28 publications
2
47
0
5
Order By: Relevance
“…A reduction in sheep numbers is often recommended [3,7,34]. Additional recommendations include sheep exclusion from severely damaged areas until vegetation has recovered [8,54], cutting thrice-yearly of undamaged, but arguably undergrazed, Molinia caerulea (L.) Moench-dominant areas to promote recovery by Calluna vulgaris (L.) Hull [47] and mixed grazing of cattle or goats with sheep [10,33]. However, cutting would not be a practical option on a site such as that studied with deep peats and steep slopes prohibiting tractor access, and grazing cattle would need to be restricted to periods when water levels are low to minimise poaching by heavier animals.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…A reduction in sheep numbers is often recommended [3,7,34]. Additional recommendations include sheep exclusion from severely damaged areas until vegetation has recovered [8,54], cutting thrice-yearly of undamaged, but arguably undergrazed, Molinia caerulea (L.) Moench-dominant areas to promote recovery by Calluna vulgaris (L.) Hull [47] and mixed grazing of cattle or goats with sheep [10,33]. However, cutting would not be a practical option on a site such as that studied with deep peats and steep slopes prohibiting tractor access, and grazing cattle would need to be restricted to periods when water levels are low to minimise poaching by heavier animals.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…From the literature, there are many data on the grazing behaviour of cattle, sheep and goats in the temperate (e.g. Celaya et al, 2007) and tropical zones (e.g. Schlecht et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A greater influence on DM intake of bite size as compared with bite rate in goats was observed by Dziba et al (2003). Celaya et al (2007) demonstrated that with a lower sward height, ewes and goats were still able to increase their BW while the BW of cows decreased. These results demonstrated that different species have variable reactions to the sward structure.…”
Section: Discussionmentioning
confidence: 88%